Case report: Abscopal response and reversal of PD-1 resistance in a patient with nephroblastoma following radiofrequency ablation - Ju, Mengyang; Sun, Mingjuan; Li, Wenfeng; Zhang, Sheng (Frontiers in Oncology, 2025)
Nephroblastoma (Wilms tumor, WT) is an extremely rare and aggressive malignancy in adults with nonspecific clinical and imaging features. There is no standard therapy for patients with progressive disease despite surgery and chemotherapy. Here, we report a unique case of a 27-year-old male patient with recurrent metastatic nephroblastoma who developed resistance to PD-1 inhibitor and targeted therapy. Radiofrequency ablation (RFA) was performed on the largest porta pulmonic lesion. Notably, 3 months post-ablation, a non-ablated pleural lesion exhibited a partial response. Follow-up confirmed PR of the pleural lesion and total disappearance of pleura-irritative symptoms. This case demonstrates a potential abscopal effect induced by RFA, in which local treatment of one tumor site coincided with systemic regression of distant, untreated lesions and reversal of prior PD-1 inhibitor resistance.